2021
DOI: 10.1021/acs.cgd.1c00534
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Influence on Piracetam Crystals: Studying by Quantum Chemical Methods

Abstract: The method developed previously for studying mechanical properties using quantum chemical calculations was applied to predict the most probable direction of deformation of the piracetam polymorphic Form II under pressure. By the analysis of the pairwise interaction energies between molecules in Form II, this structure was classified as columnar-layered. The shear deformation modeling of the strongly bound fragments in crystal packing predicted the [100] crystallographic direction with a shift energy barrier of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…Earlier, some features of the shift energy profile indicating the possibility of a polymorphic transition under pressure were found for the piracetam crystals. 38 These were a local energy minimum near the starting point, negative interaction energies between layers during the displacement, and a low shift energy barrier (Fig. 8, on the right).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Earlier, some features of the shift energy profile indicating the possibility of a polymorphic transition under pressure were found for the piracetam crystals. 38 These were a local energy minimum near the starting point, negative interaction energies between layers during the displacement, and a low shift energy barrier (Fig. 8, on the right).…”
Section: Resultsmentioning
confidence: 96%
“…According to the approach proposed earlier, 37,38 the next stage is the choice of a shear deformation direction with the plane defined using the results of the pairwise interaction energy study. A more detailed analysis of the layer recognized as BSM 1 showed that the neighboring DBUs differ in their slopes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations